Evaluasi Sistem Informasi Akuntansi Pengadaan Obat-Obatan Sebagai Upaya Meningkatkan Pengendalian Internal: (Studi Kasus Pada RSUD Bangil Kabupaten Pasuruan) - Galuh Budi Astuti; Juwi Yanto (Universitas Katolik Widya Karya Malang, 2023)
This research aims to evaluate the accounting information system for drug procurement as an effort to improve internal control at Bangil Hospital, Pasuruan Regency. This type of research is a case study. Data collection techniques through interviews, documentation and observation. Primary and secondary data sources. The problem faced is still the weak accounting information system for drug procurement at Bangil Hospital, Pasuruan Regency. This is proven by the absence of a copy of the Order Letter for the Goods Receiving Coordinator, the Contract Document which was prepared at the end, namely after the purchasing order was carried out. The cause of the problem is the lack of coordination between the Procurement Officer and the Goods Receiving Coordinator in the Warehouse Section, the need for medicines must be hastened (cito), so purchasing orders are carried out first. As a result of these problems, there is the potential for errors in receipt, fraud and failure to fulfill obligations by providers, thereby causing harm to the hospital. The results of the qualitative descriptive analysis by adding documents required for the procurement of medicines at Bangil Regional Hospital, Pasuruan Regency, improving the system and procedures for procurement of medicines at the Bangil Hospital, Pasuruan Regency, so that internal control over the procurement of medicines is increasingly optimal.